Orientation Of Rural Farmers' Behavior In The Marketing Distribution Of Wet Cocoa Beans in Pinrang Regency, South Sulawesi - Nur Faizah J; Irmayani, Irmayani; Irninthya Nanda Pratami Irwan (Cita konsultindo, 2025)
Cocoa is one of the leading commodities that plays an important role in the Indonesian economy, especially in the agribusiness and agro-industry sectors. South Sulawesi, as one of the main producers of cocoa beans in Indonesia, is facing changes in the marketing pattern of cocoa beans, especially in Pinrang Regency. This study aims to analyze the factors that affect farmers' decisions in the marketing of wet cocoa beans, the steps taken in its distribution, and the obstacles faced by farmers in Tapporang Village, Batulappa District. This study uses a descriptive qualitative approach with data collection techniques through observation, in-depth interviews, and documentation. The research informants consisted of farmer group leaders, village heads, middlemen, and agricultural extension workers. The results of the study show that the change in marketing patterns from dried cocoa beans to wet cocoa beans is influenced by weather factors, market access, and economic benefits. Farmers face obstacles in the form of price fluctuations, dependence on middlemen, and limited processing facilities. Strategies implemented by farmers in dealing with these obstacles include increasing access to market information and collaboration with stakeholders. This study provides insights for policymakers in designing interventions that support cocoa marketing stability in rural areas.